AKUNTANSI KONVENSIONAL VS AKUNTANSI SYARIAH - Indriasih, Dewi (PERMANA, 2010)
Many countries are predominantly Muslim, including Indonesia, to be un-Islamic due to political reasons and economic. But now the Islamic accounting began to show its existence (again) because the flow failures (ism): socialism, capitalism, fascism, communism. During this process of education which was originally based on religious-Islamic civilization has been replaced by a process of western secularism. Muslims now believe that the solution of existing problems is a return to Islam as a regulator of the life of Allah SWT, including accounting. Islamic accounting serves to help humans perform tasks mandated to it in a company or organization so that all activities remain in the pleasure of Allah SWT. By reviewing the conventional accounting theory, which has been the basis of accounting theory in student teaching, and assessing the Islamic accounting theory can be compared to the differences and similarities between the two. Keywords: Accounting conventional, Islamic Accounting